Mosby's 2013 nursing drug reference - Skidmore-Roth, Linda (St. Louis, Missouri : Elsevier Mosby, 2013)
There is a difference in drug handbooks. And if you want the most reliable information presented inFULL color and organized alphabetically, Mosby's Nursing Drug Reference is the only one that should be in your consideration set! With an A to Z organization, no other drug handbook helps you access reliable drug information quicker. But perhaps best of all, this full-color handbook gives you extensive drug information for over 5,000 generic and trade-name drugs - including uses, side effects, interactions, and pharmacokinetics.
Drug categories -- Individual drug monographs -- Appendixes -- Index.
Includes index.
Keywords: DRUGS HANDBOOKS, MANUALS, ETC